Evaluation of the acute dermal exposure of the ethanolic and hexanic extracts from leaves of Schinus molle var. areira L. in rats - Bras, Cristina Liliana (2011)
Ethnopharmacological relevance: Schinus molle var. areira L. (Anacardiaceae) is employed in herbal medicine for many conditions, including respiratory, urinary and menstrual disorders, and as a digestive stimulant, diuretic, astringent and antidepressant. It is also known for its topical use as wound healer, antiseptic, for skin disorders and as repellent and insecticide. In the present work, the acute dermal exposure to ethanolic and hexanic extracts from leaves of Schinus molle var. areira was studied in rats. Materials and methods: A single dose of 2000 mg/kg of body weight of ethanolic and hexanic extracts from leaves was applied on the shaved skin of male and female rats. After 24 h of exposure, the patch was removed and any sign of irritation was recorded. Behavioral and functional parameters in a functional observational battery and motor activity in an open field were assessed after the exposure to the extracts. Then, after 14 days of observation, animals were retested. Finally, histopathological studies were conducted on several organs. Results: Slight signs of erythema and edema were observed in the skin site of exposure, but they disappeared after 48 h. The exposure to the hexanic extract produced an increase in parameters of activity, rearing and arousal assessed in the functional observational battery, which reversed after 14 days. On the other hand, the ethanolic extract caused an increase in locomotor activity, reflected in a higher number of rearings performed in the open field in the evaluation carried out on Day 14. No histopathological alterations were detected in the analyzed organs. Conclusions: The results show that the acute dermal exposure of the ethanolic and hexanic extracts from leaves of Schinus molle var. areira only causes a slight and reversible skin irritation, and a mild stimulatory effect in rats. All these indicate that the topical use of these extracts would be safe.